Engineering the band gap and optical properties of a two‐dimensional molybdenum carbon fluoride MXene. Issue 5 (18th August 2022) - Anh, Doan Thi Kieu; Mui, Luong Viet; Minh, Pham Hong; Binh, Nguyen Thanh; Cadatal-Raduban, Marilou
Abstract : Using first‐principles density functional theory, the electronic and optical properties of monolayer and multilayer nanosheets of molybdenum carbon fluoride (Mo2 CF2 ), a two‐dimensional (2D) transition‐metal carbide MXene, were investigated. The unique behavior of its optical properties along with the ability to control its electronic and optical properties enhances the potential of 2D Mo2 CF2 for various applications in the fields of electronics and energy storage. Abstract : Using first‐principles density functional theory, we investigated the electronic and optical properties of monolayer and multilayer nanosheets of molybdenum carbon fluoride (Mo2 CF2 ), a two‐dimensional (2D) transition‐metal carbide MXene. The indirect band gap of the Mo2 CF2 semiconductor can be engineered by controlling the number of layers where the band gap energy changes from 0.278 eV for the monolayer to 0.249 eV for the trilayer nanosheet. The decrease in band gap energy in the multilayer is due to interlayer coupling, which splits the bands according to the number of layers. Mo2 CF2 behaves as a metal with an anomalous dispersion and high optical conductivity at incident photon energies of 0.68–2.19, 3.49–6.68 and 7.30–8.31 eV. It has a relatively low reflectivity and is absorbing over a broad range of photon energies from about 0.429 (2890), 0.387 (3204) and 0.345 eV (3594 nm) for the monolayer, bilayer and trilayer nanosheets, respectively, achieving peak absorption in the vacuum ultraviolet region at about 7.9 eV (157 nm). The optical properties of Mo2 CF2 can likewise be tuned by varying the number of layers. The unique behavior of its optical properties along with the ability to control its electronic and optical properties enhances the potential of 2D Mo2 CF2 for various applications in the fields of electronics and energy storage.